Thyroid Ultrasound Features and Risk of Carcinoma: A Systematic Review and Meta-Analysis of Observational Studies - Hazrat Bilal, Ghulam Shabbir, Irfan Amjad Lutfi, Kainat, Nadeem Siyal, Sajid Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was performed to evaluate how well thyroid nodules with nonspecific fine needle aspiration cytology and nonrandom nodules performed symptomatically for thyroid cancer. Study Design: Cross-sectional & observational study. Place and Duration: The study was conducted at Jinnah Hospital in July 2012. Methodology: We included individuals with thyroid nodules who had thyroidectomy after having their nodules assessed by the US were taken into consideration. We only took into account studies where surgical samples have been diagnosed by histology. For full-text evaluation, all of the chosen studies were accessed. Stata v11.0 software was used for all statistical analyses. Results: There were 52 observational studies totaling 12,816 nodules. 10 studies classified 1852 nodules that had uncertain cytology as a different group. With probabilities ranging from 2.15 to 3.77, all US characteristics of nonrandom nodules were substantially linked with cancer; micro calcifications, discontinuous edges, and a taller than broad form had significant particularities (Sp; 89.8 %, 85.3 %, and 98.1 %) and favorable probability ratios (LHR; 5.16, 4.19, 10.17). The one aspect with the better diagnostic efficacy was lack of flexibility (sensitivity 89.1 %, Sp 88.3 %, and positive LHR 8.19). Conclusions: Ultrasound characteristics are not an effective way to identify nodules that require fine needle aspiration cytology. To standardize elastography procedures and assess results, particularly in nodules with an undetermined cytology, more research is necessary. Keywords: Thyroid Ultrasound Features, Risk Of Carcinoma, Systematic Review, Meta-Analysis.